Pemanfaatan Internet Of Things (IoT) untuk Mengoptimalkan Sistem Irigasi dalam Menunjang Ketahanan Pangan dan Produksi Pertanian Berkelanjutan di SMKN 2 Tanah Putih - Syikhristani Syikhristani; Riris Agustin; Siti Sahara Lubis; Meli Roslianti; Yuyunisari Yuyunisari; Chusrin Irwansyah; Sari Susanti (BADAN PENERBIT STIEPARI PRESS, 2025)
The utilization of Internet of Things (IoT) technology in the agricultural sector offers an innovative solution to overcome the inefficiencies of traditional irrigation systems, which are still commonly applied in vocational education environments such as SMKN 2 Tanah Putih. This study aims to design and implement an automatic irrigation system based on IoT using soil moisture sensors, an Arduino microcontroller, and an ESP8266 communication module. The system enables real-time monitoring and control of plant watering via an internet-based application. The implementation results demonstrate increased efficiency in water usage and more optimal plant maintenance compared to conventional methods. By integrating technology into learning practices and school-based agricultural activities, this project not only supports local food security efforts but also provides a concrete contribution to the adoption of sustainable agriculture in educational institutions.